Legal Protection of Health Workers from a Criminal Law Perspective during the Health Crisis in Indonesia - Jauhari Jauhari; Afriansyah Tanjung (PDIH Untag Semarang, 2025)
This study aims to analyze the legal protection of health workers in Indonesia, particularly in light of the enactment of Law No. 17 of 2023 concerning Health. Using a normative juridical approach with statutory and conceptual analyses, the research examines the extent to which existing legal frameworks uphold the principles of legal certainty, due process, and the protection of human rights in the health sector. Legal materials include primary (laws and regulations), secondary (legal literature and expert opinions), and tertiary sources (legal dictionaries and encyclopedias). The findings indicate that Law No. 17 of 2023 offers significant normative progress by explicitly mandating state responsibility for the welfare, safety, and professional development of health workers. It encompasses both preventive and repressive legal protections, aligning with Philipus M. Hadjon’s theory of legal protection. However, practical implementation remains uneven, particularly during health crises such as the COVID-19 pandemic, where health workers experienced verbal abuse, legal threats, and inadequate support. The research concludes that while the legal substance has been improved, the effectiveness of protection depends on concrete implementation mechanisms, such as detailed regulations, supervisory systems, reporting mechanisms, and institutional support at local levels. It recommends the issuance of derivative regulations granting limited legal immunity in emergencies, establishment of legal aid units in health facilities, legal literacy training for health professionals, and a stronger culture of state and societal protection. These steps are essential to ensure that health workers can fulfill their roles safely and ethically, especially during increasingly complex public health emergencies.